DAMPAK KEPEMIMPINAN OTORITER, KECERDASAN KETIDAKPATUHAN, DAN TURN OVER INTENTION TERHADAP TURN OVER - Bambang Aviantono (Sekolah Tinggi Ilmu Ekonomi Tribuana, 2023)
This study aims to construct the assumption of the influence between authoritarian leadership and employee disobedience intelligence and turnover intention towards employee turnover in several educational institutions around Bulak Kapal, East Bekasi. A sample of 95 respondents was taken, and data were processed and analyzed using the SEM method. The theoretical findings and implications of this study indicate that there is a positive and significant influence between authoritarian leadership and turnover intention as well as turnover. However, there is no significant evidence of a direct effect of authoritarian leadership on employee disobedience intelligence. On the other hand, there is a significant direct effect between employee noncompliance intelligence and turnover intention and turnover. But, the indirect effect is not impacting through the variable of turnover intention towards turnover. ABSTRAK Studi ini bertujuan untuk membangun asumsi pengaruh antara kepemimpinan otoriter dan kecerdasan ketidakpatuhan serta turn over intention terhadap turn over karyawan di beberapa institusi pendidikan di sekitar bulak kapal Bekasi timur. Contoh 95 responden diambil dan data diolah dan dianalisis menggunakan metode SEM. Temuan teoritis dan implikasi studi ini menunjukkan bahwa terdapat pengaruh positif dan signifikan antara kepemimpinan otoriter dan turn over intention serta turn over. Namun, tidak ada bukti signifikan efek langsung dari kepemimpinan otoriter terhadap kecerdasan ketidakpatuhan karyawan. Disisi lain terdapat pengaruh langsung signifikan antara kecerdasan ketidakpatuhan terhadap turn over intention dan turn over. Namun pengaruh tidak langsung tidak berdampak melalui variable antara turn over intention terhadap turn over.